Public Interest Litigation (PIL) as Strategic Legal Mechanism on Women’s Socio-Economic Rights in Nigeria: Making a Case for Girl Child Education - Adeniyi, Olayinka O.; Olomola, Omolade O. (European Scientific Journal, ESJ, 2020)
The percentage of girl child illiteracy is higher in girls than boys in Africa. This is particularly so in Nigeria. It is trite that Girl-child issues are generally confined within women’sright in Nigeria. As important as education isto life and humanity, it however falls under socio economic rights in Nigeria, which by virtue of the interpretation of constitutional provisions are argued as non-justiciable. Hence, accessing education for the girl child as a justice system or mechanism has been a challenge in the country. In recent times, some countries have directed public Interest litigation into fighting some socio-economic issues. This is a development which has not been practiced earlier and success is being recorded. It can be said that Public Interest litigation has been able to deal particularly with the challenge of locus standi which hasto do with the opportunity of accessing justice on some rights issues. Focusing on girl-child education in Nigeria, as a socio-economic rights issue to which access to justice is a challenge and to which legal strategic mechanism can bring a change is a positive one. The paper looks at the impact of African girl child illiteracy at this time in the global environment for sustainable development, the legal impediments to accessing justice on socio economic rights; recent legal mechanisms as best practices of getting socioeconomic rights enforced in some developed countries; innovative and emerging ways of its realization and enforcement in Nigeria. It proffers suggestions on legal and strategic litigation introduction or enhancement mechanism, the challenges if any and the gains more importantly of the public litigation procedure. The paper attempts a desktop and library-based approach in a comparative analysis of legal framework, policies on education, literature review of existing scholarship, case study on strategic litigation in some jurisdictions on socio economic rights and applies it to suggest Public Interest Litigation PIL for girl child education in Nigeria. The paper is germane for women’s right advancement, law and or policy reform and citizen empowerment in Nigeria and Africa at large.